2019
DOI: 10.21203/rs.2.14586/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study of patients' satisfaction in different levels of hospitals in Beijing: Why do patients prefer high-level hospitals?

Abstract: Background: In order to promote the vertical flow and integration of medical resources, Beijing built medical alliances since 2012, but this practice did not change the disordered state of medical treatment. Patients are still willing to go to high-level hospitals for medical treatment. What causes patients to prefer high-level hospitals? Through previous research, patients' choice of medical treatment was affected by patients' satisfaction. Therefore, we compared the patients' satisfaction in different level … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…It is recommended that grassroots hospitals improve the circumstances and service capability of township health facilities, as well as optimize the organization of human resources in medical institutions. Medical and health resources are usually divided into three categories: medical and health financial resources, medical and health people resources, and medical and health material resources The research found that hospitals with better grades have higher medical expectations, higher levels of satisfaction, and higher levels of faith in medical technology, based on a survey of patient satisfaction with hospitals of various grades [3]. Hospital can improve patient satisfaction by optimizing resource allocation and utilization and adjusting medical service and management strategy [4].…”
Section: Medical Resourcesmentioning
confidence: 99%
“…It is recommended that grassroots hospitals improve the circumstances and service capability of township health facilities, as well as optimize the organization of human resources in medical institutions. Medical and health resources are usually divided into three categories: medical and health financial resources, medical and health people resources, and medical and health material resources The research found that hospitals with better grades have higher medical expectations, higher levels of satisfaction, and higher levels of faith in medical technology, based on a survey of patient satisfaction with hospitals of various grades [3]. Hospital can improve patient satisfaction by optimizing resource allocation and utilization and adjusting medical service and management strategy [4].…”
Section: Medical Resourcesmentioning
confidence: 99%